A Psychological Study of Chinese Audience Reception of The Cross-Cultural Film Everything Everywhere All at Once: Why Cultural and Communication Adaptation Fail? - Quan, Rao; Rui, Chen (Published by Confucius Institute UNS, 2023)
In most movies, the